The Impact of Natural Stone Waste Pollution on The Distribution and Abundance of Phytoplankton in Cirebon District - Wahyuningsih, Sri (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
The natural stone industry in Cirebon Regency produces large amounts of liquid waste which is directly discharged into rivers. The sludge resulting from the natural stone washing process contains high levels of suspended material, causing water pollution and disrupting the life of aquatic organisms including phytoplankton. Phytoplankton have an important ecological role as primary producers and food sources for other organisms, where their distribution and abundance are strongly influenced by various environmental factors. This research aims to determine the impact of natural stone waste pollution on the abundance and structure of phytoplankton communities in several water locations in the Jamblang watershed. A total of three observation stations were selected using a purposive sampling method at several points in the Jamblang Watershed, Cirebon Regency. The research results showed that phytoplankton were found at all observation stations with the identified types consisting of four classes, namely Bacillariophyceae (16 genera), Chlorophyceae (4 genera), Cyanophyceae (4 genera) and Euglenophyceae (2 genera). Bacillariophyceae is the most diverse class, while Oscillatoria sp. from the Cyanophyceae class was found to be the most abundant at all stations. The abundance of phytoplankton ranged between 716,587 - 1,332,122 cell/m3, where the highest abundance was found at station 2. The ecological index showed that the diversity and uniformity of phytoplankton at all stations was in the medium category. Species dominance at station 2 and station 3 is low, while at station 1 tends to have greater dominance than at other stations. Overall, from the results of calculations of abundance and community structure, several phytoplankton species show resistance to water conditions polluted by natural stone waste and other anthropogenic waste, especially from the Bacillariophyceae and Cyanophyceae classes which can be used as indicators of polluted waters.